Lessons From a 10-yr Invasive Species Webinar Program: Emerald Ash Borer University. Issue 3 (16th February 2021) - Barnes, Elizabeth E; Usborne, Robin; Stone, Amy; Sadof, Clifford S
Abstract: Information about invasive species needs to be spread rapidly across a wide geographic area following an invasion. However, in-person events can be time-consuming and costly for the participants, organizers, and presenters. Online programming like webinars can bridge this gap, but there is limited published data on how best to run these programs. We report on a 10-yr webinar program, Emerald Ash Borer University, and offer suggestions for improving their effectiveness as a communication tool. Webinar participants viewed the webinars positively and undertook recommended management actions. In addition, most of our survey respondents extended the reach of this program by widely sharing the information from the webinars. Posting the webinars on popular streaming platforms greatly extended their reach long after the live viewing event. Despite their longevity, viewers of recorded videos watched them differently than those viewing live events. We suggest modifying the format of future webinar presentations to accommodate these differences to improve information transfer.